Site‐specific recombination for cloning of large DNA fragments in vitro. Issue 6 (26th May 2015) - Dai, Ruixue; Zhang, Bo; Zhao, Guoping; Ding, Xiaoming
<x xml:space="preserve">Abstract</x> Natural‐product biosynthetic gene clusters are composed of large DNA fragments, which are difficult to synthesize in vitro. In this study, a Streptomyces phage site‐specific ΦBT1 integrase‐mediated recombination reaction was employed to obtain the 55 kb erythromycin biosynthesis gene cluster of Saccharopolyspora erythraea. Genome fragments inserted by ΦBT1 integrase recognition att‐sites (attachment site of bacteria and attachment site of phage) and two selectable markers (aphII gene and aac(3)IV gene) on both sides of the target gene cluster were extracted and subjected to an in vitro site‐specific recombination reaction to yield a plasmid pZB201 carrying the erythromycin biosynthesis gene cluster. This technique avoids mutations caused by PCR and limitations caused by restriction enzyme sites, making heterologous expression much more effective and convenient.